Authentic information on the natural-technogenic geological environment as a factor of reducing environmental risks - Соколов, В. А.; Удалов, И. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. An important component of environmental safety is the state of protection of the natural and man-made geological environment (ESGE) from the influence of dangerous natural and technogenic geological processes. At present, there are 327 cities in Ukraine that need protection from certain dangerous geological processes (groundwater underflooding, landslide displacement, subsidence of base soils, etc.). [1-4] One consequence of this is the deformations and accidents of housing and utility buildings and industrial structures. Obviously, engineering and technical security of housing, along with other parameters of life safety is the basic human need.The safety of construction, reconstruction, operation of structures, territories protection from hazardous natural and man-caused processes, assessment of the impact of construction and reconstruction facilities on the environment, risk assessment should be based on complete and reliable data on the state and dynamics of ESGE, which is the subject of engineering research [ 14]. At the same time, there is a group of factors systematically adversely affecting the receipt of reliable information in this area. This article is devoted to a detailed consideration of this problem. History of the research of the problem. Problems of engineering geology and hydrogeology of urban areas, changes in the geological environment under the influence of human activity are revealed in the works of F. Kotlova, V. Krutova, V. Osipova, E. Yakovlev and others. A significant specificity of the research of the natural and man-made environment (engineering and technical surveys) is indicated by P. Konovalov, V. Ulitsky, M. Solodukhin, G. Strizhelchik, etc. Problems of engineering research and protection of historical buildings in the construction of new and reconstruction of the existing buildings remain relevant even now, especially for such large cities as Kyiv, Kharkiv, Dnipro, Donetsk, etc. The purpose of the article is to substantiate the need for a reliable assessment of the state and dynamics of changes in the natural and technical geological environment. Classification of existing factors systematically adversely affecting the receipt of reliable information and determining ways to solve the problem is aimed at reducing geotechnical and environmental risks. All large cities in Ukraine need protection from the manifestation of certain dangerous geological processes (underflooding by underground waters, landslide displacement, subsidence of base soils, etc.). The safety of construction and operation of facilities, assessment of the level of environmental hazard should be based on reliable information on the state and dynamics of the natural and man-made geological environment. To determine the severity of the environmental situation, the degree of deviation of an object or environment from a certain norm is usually used. It is important to know how far the object approached the level of destruction of its structure. The criterion for assessment can be the resource of the stability of the geological environment, determined by the permissible impact impulses (water inflow, application of static and dynamic loads, temperature effects, etc.). Today in Ukraine there is a group of factors systematically adversely affecting the receipt of reliable information on the conditions of construction sites. This can lead to plant accidents or to significant unnecessary security costs, up to and including the abandonment of construction. These factors include: 1. Construction in all free areas with complex engineering and geological conditions in the central parts of cities, with maximum use of underground space; 2. Increasing the weight of reconstruction of existing buildings in the total volume of construction. It should be kept in mind that engineering surveys for reconstruction, having specific features, make them more complex than surveys for new construction sites; 3. A complex of administrative, economic and social factors associated with the systems of attestation of specialists, quality control, work in a market economy, etc. To create objective conditions that reduce the degree of geotechnical and environmental risks, it is necessary to implement a set of measures at the state level.